(untitled) (International Journal of Engineering and Computer Science, 2015)
A Novel Framework for investing the electronic compensation for a 10.7-Gb/s system using a directly modulated LASER (DML) approach. The significant usage of digital signal processing and large signal rate equations helps in reducing the non linear distortion which outcomes from direct modulation of laser and to generate an appropriate modulating current. After successful generation of modulation current the proposed scheme is then utilized in a novel look up table optimization scheme for electronic dispersion precompensation. Finally the simulation results shows that the proposed theoretical work shows the compensation of 250km approximately using a 21.4GSa/s DIGITAL TO ANALOG CONVERTER and simultaneously 350km approximately using a 42.8GSa/s DAC. Finally the proposed work shows that approximately using a 42.8GSa/s DIGITAL TO ANALOG CONVERTER is sufficient forexploiting the full potential for ELECTRONIC PRE-COMPENSATION using a DML.